IMPROVING ENGLISH FOR TOURISM IN INDONESIA: KNOWING THE BADUY CULTURE - Wawat Srinawati; Idun Suwarna; Muhammad Usman (Jurnal Sociohumaniora Kodepena (JSK), 2021)
English for tourism is to fulfil students’ need to learn English for specific purposes. Baduy people are people who live in disconnection in the inside of South Banten. The Baduy public are notable as individuals who can oversee woods and their current circumstance well. This study aims to find out the Baduy culture and climate and how they use it intelligently and admirably. The fundamental strategy used is a review technique with several PRA procedures.The examination was directed in Kanekes Village, Leuwidamar District, Lebak Regency. Banten Province. The information gathered, both essential information and auxiliary information, were then examined by subjective spellbinding investigation. The space of ​​Baduy is 5,101.8 hectares, with a populace of around 5,000 individuals spread north of 10 towns. The whole populace makes money as dry rice ranchers (huma) with a moving development framework controlled by custom. In dealing with their current circumstance, the Baduy people group holds fast to standard guidelines, the pith of which is severe spatial game plans for ensured regions and developed regions.